Penerapan Algoritma Minimax Pada Permainan Checkers - Joel Parlinggoman Aritonang; Rinna Rachmatika (CV. Multi Kreasi Media, 2023)
Chekeres is a type of board game, which in this type of game relies on strategy as its main element. This game of checkers is generally played by two people with the objective being to spend the opponent's pieces. A checkers game made using a certain AI (Artificial Intelligence) implements the minimax algorithm. This minimax algorithm is used to make choices in order to minimize the possibility of losing the maximum value, which will describe where if a player experiences income, other players will experience a loss of that income. To reduce the scope of the search on the minimax algorithm, an algorithm called alpha-betha was developed as a solution to reduce the number of nodes in the search tree. In the checkers game, this algorithm will determine the steps taken by AI to generate maximum income by considering the possible steps that can be taken next. The application of the minimax algorithm in the game of checkers is made based on the Minimax procedure with the aim of getting the best move from the existing position. The minimax algorithm is based on a zero-sum game, which means that if one player wins, the other player loses, if one player gets 1 point then the other player gets -1 point.